Single enantiomer propeller-shaped polynuclear complexes as catalysts-proof-of-concept for enantioinduction in a Michael addition reaction - Joe Maddocks; Mohan Mahesh; Stavroula I. Sampani; Alexander C. Dixon; Christian D.-T. Nielsen; Prashant Kumar; Geoffrey R. Akien; John Spencer; Alaa Abdul-Sada; John F. C. Turner; Alan C. Spivey; George E. Kostakis (Royal Society Open Science)
We report a family of propeller-shaped polynuclear metal complexes whose overall chirality is dictated by a single stereogenic centre within their component amino alcohol-ligand. These topologically intriguing complexes are readily prepared in enantiomerically pure form and are shown here to catalyse the conjugate addition of barbituric acids and their derivatives to nitroalkenes, with a catalyst loading of 1 mol%. Although only low levels of enantioinduction are observed, control experiments indicate that the enantioselectivity is dictated by the overall topology of the complex and not governed by binding to the tetrametallic entity, heralding a potentially new mode of catalysis.